Changes in the Traditional Ceremony of Mesiwah Pare to Mesiwah Pare Gumboh Dayak Deah, Liyu Village, Halong District, Balangan Regency, South Kalimantan - Muhammad Aulia Rahman; Bambang Subiyakto; Heri Susanto (JURNAL PENDIDIKAN IPS, 2025)
This study examines the transformation of the traditional Mesiwah Pare ritual into Mesiwah Pare Gumboh among the Dayak Deah community in Liyu Village, South Kalimantan. Using a descriptive qualitative approach, the research identifies significant impacts across three main dimensions: social, cultural, and economic. Socially, the ritual shifted from a kinship-based practice to a more structured collective celebration, fostering public solidarity while reducing the intimate familial role of individual farmers. Culturally, the integration of performing arts and festival formats has created a duality between preserving cultural identity and the potential erosion of sacred values. Economically, the ritual transitioned from a self-funded tradition to an event supported by sponsorships and government programs, opening local economic opportunities but raising concerns over cultural commodification. These findings highlight that cultural adaptation can strengthen community participation and promote local heritage, though it still requires careful strategies to preserve spiritual values amid modernization.